Fall prevention for people with learning disabilities: key points and recommendations for practitioners and researchers. Issue 2 (3rd April 2018) - Finlayson, Janet
Abstract : Purpose: The purpose of this paper is to provide a narrative review of what is currently known about the high rates of falls, and fall injuries, which are experienced by people with learning disabilities (LDs) throughout their lives. Design/methodology/approach: Narrative review. Current evidence is summarised as key points and recommendations for practitioners and researchers. Findings: People with LDs experience similar rates of falls as older adults in the wider population, but throughout their lives, or at an earlier age. Originality/value: Key points and recommendations are summarised for practitioners and researchers to promote fall prevention strategies and interventions for people with LDs.